Evaluation of Pyrolysis Temperature and Time on The Quality Improvement of Calliandra Wood Charcoal Briquettes as An Alternative Energy Source - Murda, Rio Ardiansyah; Pasaribu, Try Vista Ulina Br; Wahyuningrum, Maeda; Zen, Muhammad Rizky; Maulana, Sena; Rinaldi, Nino; Maulana, Muhammad Iqbal; Munawaroh, Khoryfatul; Lizardi, Fathi; Faedloni, Akbar Ash Shiddiqi (Universitas Jenderal Soedirman, 2026)
ABSTRACT. Calliandra (Calliandra calothyrsus) wood is a promising biomass feedstock due to its abundance and high calorific value. This study investigated the effects of pyrolysis temperature (400 °C and 500 °C) and residence time (30 and 60 minutes) on the quality of calliandra charcoal briquettes. Biomass was carbonised, mixed with 15% cassava starch binder, pressed, and oven dried. The briquettes were evaluated for yield, density, moisture, ash, volatile matter, fixed carbon, calorific value, combustion rate, and structural changes. Results showed that all parameters except yield were significantly influenced by temperature and time. FTIR analysis revealed increased aromatisation at higher pyrolysis conditions, while XRD indicated reduced cellulose crystallinity and the emergence of calcite and silica phases. The briquettes exhibited densities of 0.62–0.63 g/cm³, moisture contents of 2.14–2.73%, ash 3.55–4.91%, volatile matter 16.32–25.11%, fixed carbon 68.60–76.63%, calorific values 7,856–7,978 cal/g, and combustion rates 0.08–0.09 g/min. The condition of 400 °C for 30 minutes offered the most balanced performance, while 500 °C for 60 minutes yielded the highest carbonisation and energy content. These findings highlight that moderate pyrolysis conditions can produce efficient, high-quality briquettes with low energy input. Keywords: Biomass, calliandra wood, energy, pyrolysis, wood charcoal briquettes